Learning Rare Events - Alvaro Sandroni (Northwestern University, Kellogg School of Management, Center for Mathematical Studies in Economics and Management Science, 1997)
In this paper I consider a dynamically complete market model without intrinsic uncertainty. The only uncertainty is modelled by sunspots. Agents' beliefs are heterogeneous, but eventually become homogeneous in the sense that agents' beliefs are identical in the limit. I show that if some states of nature occur rarely then arbitrarily large market crashes may occur infinitely often. This result contrasts with Cass and Shell's (83) results which show that when beliefs are homogeneous, in complete markets without intrinsic uncertainty, sunspots do not matter.
Keywords: D83; 330; Convergence to Rational Expectations; Learning; Rate Events; Market Crashes